Operational Productivity Index Patterns in Logistics Services Using Mundel Model: Pola Indeks Produktivitas Operasional dalam Layanan Logistik Menggunakan Model Mundel - Boy Isma Putra; Ach. Yoga Ardiansah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Productivity measurement is essential for logistics companies to maintain operational performance and resource efficiency. Specific Background The operational activities of Ninja Xpress during 2024 experienced fluctuating output and rising costs of labor, energy, and maintenance, requiring systematic evaluation. Knowledge Gap Previous studies discussed the Marvin E. Mundel method separately from strategic analysis, while integrated measurement and strategy formulation within a single logistics company remain limited. Aims This study measures operational productivity and formulates improvement strategies using the Marvin E. Mundel quantitative approach combined with SWOT analysis. Results The calculated productivity index shows monthly variation, with the highest value recorded in September at 129.81% and the lowest in April at 97.56%, while the SWOT matrix positions the company in Quadrant I, indicating strong internal capacity and favorable opportunities. Novelty The integration of numerical productivity indices with structured internal–external evaluation provides a comprehensive diagnostic framework. Implications The findings support data-driven decision making, periodic performance monitoring, and strategic planning to strengthen logistics operations and competitiveness. Keywords: Operational Productivity, Marvin E Mundel Method, SWOT Analysis, Logistics Operations, Productivity Index Key Findings Highlights: Monthly values varied widely across the 2024 period Strong internal capabilities aligned with external opportunities Integrated quantitative and strategic assessment guides planning